Program Pengembangan Sabun Tangan Berbasis Eco-enzyme dari Sampah Organik di Kelurahan Gebang Putih, Surabaya - Gideon Setyo Budiwitjaksono; Dwi Mulyati Ningrum; Amanda Meiliya; Ely Nanda Khamdiyah; Esya Ananta Riski Tyanti (Inovasi Sosial : Jurnal Pengabdian Masyarakat, 2024)
Eco-enzyme-Based Hand Soap Development Program from Organic Waste in Gebang Putih Village, Surabaya, aims to reduce organic waste and increase public awareness of the importance of environmentally friendly products. Eco-enzymes, which are produced from the fermentation of organic waste such as fruit and vegetable scraps, are used as the main ingredient in the manufacture of hand soap. This process not only reduces the amount of waste that ends up in landfills, but also results in a safe and effective product for hand hygiene. This research involves several stages, including the collection and sorting of organic waste, the fermentation process to produce eco-enzymes, and the formulation and testing of the resulting hand soap. The people of Gebang Putih Village are actively involved in every stage of the process, both through education and direct participation in soap making. The results of the program show that eco-enzyme-based hand soap has good quality and is well received by the community. In addition to providing solutions to the problem of organic waste, this program also contributes to improving the local economy by providing new business opportunities for the community. Thus, this program is expected to be a model that can be replicated in other regions, in order to support environmental sustainability and community welfare